Pengaruh Cash Ratio dan Pertumbuhan Laba Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Mufidah, Mufidah; Febrianti, Ira; Adisetiawan, R. (Universitas Batanghari Jambi, 2024)
This study eexamines the effect of the cash ratio, and profit growth on company value and see whether company size can moderate the cash ratio and profit growth on company value. This research takes as its object the companies that are members of the food and beverage industry listed on the Indonesia Stock Exchange for the period 2017 - 2021 which have made consecutive profits. Based on the research results, the cash ratio does not affect company value, as well as profit growth does not affect company value. Apart from that, company size does not strengthen the relationship between the cash ratio, and profit growth on company value.